Capital management risk and value of the firm: Perspectives from private equity financial firms in Kenya - Florence Waitherero Kariuki; Stephen Muchina; Stephen Macharia (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study sought to explore the effect of capital management risk on value of the firm among private equity financial firms in Kenya. Design/methodology/approach: Anchored on the agency theory and guided by positivism research philosophy, descriptive research design as well as causal research design, the study surveyed 115 savings and credit societies regulated by Sacco Societies Regulatory Authority. A panel regression model detailing the interaction between capital risk management and firm's value was set. Findings: The study found that capital management risk significantly affects value of SACCOs in Kenya such that a unit change in capital adequacy ratio increases value of SACCO. Originality/value: The results of the study supported the propositions of agency theory which postulates that goal incongruence and asymmetric information may generate agency problems forcing the owners of the firm to incur agency costs which reduce the cash flows available for investment leading to sub-optimization and thus reducing the value of the firm. We recommend management of SACCOs in Kenya to seek to improve their capital adequacy ratio by increasing their tier one and tier two capital so as to increase their overall core capital.
Keywords: G32; G39; G23; G29; 330; Capital Adequacy Ratio; Capital management risk; Firm value and SACCO